Integrasi Data Absensi dan Perijinan Karyawan pada Aplikasi Kepegawaian Menggunakan Metode Prototype - Samsuri Yahya (Jurnal Informatika Universitas Pamulang, 2024)
This study aims to develop an integrated web-based personnel information system to manage employee absence and permit data in the company S M, which currently still uses a manual and non-integrated system. The research method used is Research and Development (R&D), with an object-based system approach using the Unified Modeling Language (UML) for system documentation. The system was developed using the Prototype Method, with PHP and MySQL-based technology to ensure the system is easy to access and develop. The sampling technique was carried out through direct observation and interviews with the company's HRD department to obtain a comprehensive picture of the needs of the personnel system. The final result is expected to facilitate the management of personnel data, including permit applications and absence reports, as well as improve the efficiency of HRD work in the company.